2014
DOI: 10.3233/nre-141178
|View full text |Cite
|
Sign up to set email alerts
|

Using clinical and robotic assessment tools to examine the feasibility of pairing tDCS with upper extremity physical therapy in patients with stroke and TBI: A consideration-of-concept pilot study

Abstract: BACKGROUND: Transcranial direct current stimulation (tDCS) may provide a safe, non-invasive technique for modulating neural excitability during neurorehabilitation. OBJECTIVE: 1) Assess feasibility and potential effectiveness of tDCS as an adjunct to standard upper extremity (UE) physical therapy (PT) for motor impairments resulting from neurological insult. 2) Determine sustainability of improvements over a six month period. METHODS: Five participants with chronic neurologic insult (stroke or traumatic brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 48 publications
2
48
0
1
Order By: Relevance
“…Table 2 details seven tDCS studies. 39 45 Six clinical studies were found in the chronic phase of TBI, and there was only one study 39 in the subacute phase. In contrast to TMS studies, most tDCS studies were randomized controlled trials or crossover studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 details seven tDCS studies. 39 45 Six clinical studies were found in the chronic phase of TBI, and there was only one study 39 in the subacute phase. In contrast to TMS studies, most tDCS studies were randomized controlled trials or crossover studies.…”
Section: Methodsmentioning
confidence: 99%
“…All patients received bihemispheric tDCS over M1 paired with standard upper extremity physical therapy (24 sessions of 40 minutes, three times per week). They monitored lasting motor function improvement 45 and reported positive results 6 months after tDCS stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been similar variability in the reports of combined rehabilitative training and tDCS in the injured population. Several studies have reported greater behavioral improvement with combined tDCS and training, compared with training alone, in motor function (Middleton et al, 2014 ; Kasashima-shindo et al, 2015 ), motor function associated electrophysiology measures (Kim and Ko, 2013 ), aphasia (Wu et al, 2015 ), neglect (single case report) (Brem et al, 2014 ), and attention (Park et al, 2013b ). However, some of the positive studies were conducted on extremely small numbers ( n < 10).…”
Section: Brain Lesions After Stroke and Injurymentioning
confidence: 99%
“…Los métodos de evaluación del movimiento de la ES convencionales dependen de la experiencia y la subjetividad de los médicos o terapeutas evaluadores. Las evaluaciones de la función motora de la ES se centran en pruebas clínicas que dependen en gran medida de los criterios del examinador (Middleton et al, 2014) y requieren que un terapeuta califique a los pacientes mientras estos realizan tareas y actividades específicas.…”
Section: Introductionunclassified